Effect of magnetic field in hard water treatment - Zavaleta, Mery (1998)
Magnetic Water  treatment is know for over a century, even though, actually no one knows exactly how it works. One of the naim applications is to suppress water-scale deposition on the inner surface of boilers, heat exchangers and pipelines. In the paper we report some experiments concerning the effectivity of the magnetic treatment in the reduction of water scale deposition. The applied diagnostic methods were: Observation of the turbidity factor (Tyndall efect). Cristallographic observations under polarized light. structural measurements (Debye-Scherrer spectra) and chemical composition.